Effect of Intravenous or Perivascular Injection of Synthetic Adrenocorticotropic Hormone on Stimulation Test Results in Dogs. (13th April 2017) - Johnson, C.M.; Kass, P.H.; Cohen, T.A.; Feldman, E.C.
Abstract : Background: Standard protocols for adrenocorticotropic hormone (ACTH) stimulation testing (ACTHst) often involve intravenous (IV) injection of corticotropin. ACTH might be unintentionally injected into the perivascular (PV) space. Objective: To compare stimulation test results after IV and PV injections of ACTH. Animals: Twenty privately owned dogs were studied: 10 healthy and 10 with trilostane‐treated naturally occurring hyperadrenocorticism (HAC). Methods: Prospective study. Each of 20 dogs underwent 2 ACTHst not <4 nor more than 14 days apart. Five healthy and 5 HAC dogs had an IV ACTHst first and PV second; 5 healthy and 5 HAC dogs had a PV ACTHst first and IV second. Blood samples for measurement of serum cortisol concentration were collected before and 1 hour after ACTH administration. Results: No significant difference in results was demonstrated when comparing serum cortisol concentrations after IV and PV ACTH administration in all 20 dogs (median μg/dL; interval μg/dL: 8.2; 1.4–17.4 versus 7.8; 0.9–16.9; P = .23). No significant difference in results was demonstrated when comparing serum cortisol concentrations after IV and PV ACTH administration in the 10 healthy dogs (median μg/dL; interval μg/dL: 10.9; 7.3–17.4 versus 10.6; 7.1–16.9; P = .54) or in the 10 HAC dogs (median μg/dL; interval μg/dL: 6.3; 1.4–8.6 versus 5.2; 0.9–8.7; P = .061). Conclusions and Clinical Importance: Perivascular administration of ACTH does not significantly alter stimulation test results in healthy dogs or in dogs with HAC undergoing therapy with trilostane.